KINERJA KEUANGAN PERBANKAN (PERBANDINGAN PADA BANK RAKYAT INDONESIA Tbk DAN BANK CENTRAL ASIA Tbk) - Nurhayani Lubis (Jurnal Ekonomi Bisnis Manajemen Prima, 2021)
This study was conducted to compare the financial performance of BCA and BRI banks. where, these two banks are both in book IV in the bank grouping. The banks in this book group are the banks with the largest capital in Indonesia. The financial ratios used in this study are ROA, LDR, and CAR. the three ratios represent the ratio of profitability, solvency, and liquidity. The data analysis used in this research is independent samples t test. And the results of the study indicate that the three ratios used have significant differences between BRI and BCA banks.